2020
DOI: 10.1111/joim.13026
|View full text |Cite
|
Sign up to set email alerts
|

What proportion of patients with chronic noncancer pain are prescribed an opioid medicine? Systematic review and meta‐regression of observational studies

Abstract: Mathieson S, ). What proportion of patients with chronic noncancer pain are prescribed an opioid medicine? Systematic review and meta-regression of observational studies (Review). J Intern Med 2020; 287: 458-474.Guidelines now discourage opioid analgesics for chronic noncancer pain because the benefits frequently do not outweigh the harms. We aimed to determine the proportion of patients with chronic noncancer pain who are prescribed an opioid, the types prescribed and factors associated with prescribing. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 81 publications
(137 reference statements)
1
41
0
Order By: Relevance
“…As nation's economies develop, and commercial influence is inadequately regulated, clinicians often implement highly technical but low-value options rather than ensuring that the high-value fundamentals are also accessible [7]. Health systems have also been slow in ceasing support for treatments that are no longer supported by evidence and carry risk of harm, such as lumbar spinal fusion for non-specific back pain and opioid prescribing for chronic non-cancer pain [8,9]. Although clinical guidelines and Models of Care (system-level frameworks that guide service delivery for specific conditions [10]) recommend high-value options as preventive public health strategies and first-line treatments (e.g., exercise and weight loss for osteoarthritis pain), many health systems fail to achieve this.…”
Section: Box 1 Definitions Of Levels Within a Health Systemmentioning
confidence: 99%
“…As nation's economies develop, and commercial influence is inadequately regulated, clinicians often implement highly technical but low-value options rather than ensuring that the high-value fundamentals are also accessible [7]. Health systems have also been slow in ceasing support for treatments that are no longer supported by evidence and carry risk of harm, such as lumbar spinal fusion for non-specific back pain and opioid prescribing for chronic non-cancer pain [8,9]. Although clinical guidelines and Models of Care (system-level frameworks that guide service delivery for specific conditions [10]) recommend high-value options as preventive public health strategies and first-line treatments (e.g., exercise and weight loss for osteoarthritis pain), many health systems fail to achieve this.…”
Section: Box 1 Definitions Of Levels Within a Health Systemmentioning
confidence: 99%
“…A systematic review found that the average 1‐month prevalence of moderate‐to‐severe non‐cancer chronic (CNCP) pain was 19% in Europe (Reid et al., 2011). Analgesics such as opioids are frequently used to treat CNCP (Mathieson et al., 2020). There has been an increase in opioid prescriptions in first world countries in the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review which included 42 studies (28 from the USA, 9 from European countries, 3 from Canada and 1 each from Australia and India) reported that almost one-third of patients with chronic pain are prescribed opioids [5]. There is significant harm associated with opioid use.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited effective methods for managing chronic pain [9]. Thus, in developed countries, compassionate advocacy for better treatment of chronic pain influenced the liberalization of laws governing the opioid prescriptions, and along with aggressive marketing of opioid formulations, resulted in relying on opioids for chronic pain relief [5].…”
Section: Introductionmentioning
confidence: 99%